LESBIAN, GAY, BISEKSUAL DAN TRANSGENDER: TINJAUAN TEORI PSIKOSEKSUAL, PSIKOLOGI ISLAM DAN BIOPSIKOLOGI - Muhammad Rizki Akbar Pratama; Rahmaini Fahmi; Fatmawati Fadli (Psikis : Jurnal Psikologi Islami, 2018)
The rise of LGBT case in Indonesia, attracted the attention of researchers to see how the view of psychology about LGBT. This study is a literature review research using relevant reference theories and publications in the field of Psychosexual, Islamic Psychology, and Biopsychology. According to the psychosexual perspective, humans are inherently bisexual. A person to be able to express himself as LGBT or heterosexual is when he is in phallic phase, where the point of pleasure is in the genitals. Based on the Islamic psychology, LGBT behavior is a type of ammara personality; dominated by lust 55%, assisted by 30% of mind power, and 15% of qalbu. While based on biopsychological point of view, LGBT behavior is not influenced by hormones but occurs due to changes in brain structure caused by experience and environment called plasticity, where the behavior of a person is able to change the shape of the human brain itself. From the results of the literature review above shows that LGBT is an abnormality of sexual orientation that is influenced by one's experience and environment.